2001
DOI: 10.1094/phyto.2001.91.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Host Specialization in the Charcoal Rot Fungus, Macrophomina phaseolina

Abstract: To investigate host specialization in Macrophomina phaseolina, the fungus was isolated from soybean, corn, sorghum, and cotton root tissue and soil from fields cropped continuously to these species for 15 years in St. Joseph, LA. Chlorate phenotype of each isolate was determined after growing on a minimal medium containing 120 mM potassium chlorate. Consistent differences in chlorate sensitivity were detected among isolates from different hosts and from soil versus root. To further explore genetic differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
156
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(182 citation statements)
references
References 25 publications
21
156
2
3
Order By: Relevance
“…Some workers also related variability to the phenomena of host specialization in M. phaseolina. Su et al, (2001) found host specialization in maize on the basis of pathogenic, genetic, and physiological differences. Similarly, Cloud and Rupe (1988) analyzed host specialization in soybean.…”
Section: Genotypementioning
confidence: 99%
“…Some workers also related variability to the phenomena of host specialization in M. phaseolina. Su et al, (2001) found host specialization in maize on the basis of pathogenic, genetic, and physiological differences. Similarly, Cloud and Rupe (1988) analyzed host specialization in soybean.…”
Section: Genotypementioning
confidence: 99%
“…The area under the disease progress curve shows that the most Means followed by the same letter in each column are not significantly different, according to Tukey'sHSD test (p ≤ 0.05). 1 Parameters assessed 10 weeks after inoculation. 2 Reduction calculated based on uninoculated control plants.…”
Section: Growth Chamber Trialmentioning
confidence: 99%
“…is a plant pathogen that attacks a wide range of hosts in more than 500 plant families. It affects crops such as soybean, sorghum, corn, cotton [1], jute [2], sunflower [3], sesame [4], common bean [5], melon [6] and strawberry [7], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus showed insensitivity to the active ingredients of fluquinconazole, metalaxyl, thiram and tolyfluanid. sesame, sunflower, bean, cotton, black lentil, chili pepper, maize, tall grass prairie, tomato and watermelon, among others, affecting more than 500 plant species (Machado 1980, Singh et al 1990, Wyllie 1993, Smith & Carvil 1997, Su et al 2001, Saleh et al 2010, Mahdizadeh et al 2011.…”
Section: Introductionmentioning
confidence: 99%